Nonlinear low-frequency structures in the auroral plasma in the presence of an oxygen beam including charge separation - Moolla, S.; Bharuthram, R.; Singh, S.V.; Lakhina, G.S.; Reddy, R.V. (My University, 2010)
Observations from the Fast Auroral SnapshoT FAST satellite indicate that the parallel and perpendicular to the Earth’s magnetic field electric field structures exhibit a spiky appearance. In this study, a magnetized plasma system consisting of protons, electrons, and a cold oxygen ion beam is considered. Both background electrons and protons are treated as hot species with Boltzmann density distributions. The dynamics of the oxygen ion beam is governed by the fluid equations. Effect of charge separation is studied on nonlinear fluctuations arising from a coupling of ion cyclotron and ion-acoustic waves. A scan of parameter space reveals a range of solutions for the parallel electric field from sinusoidal to sawtooth to highly spiky waveforms. The inclusion of charge separation effects tends to in most cases increase the frequency of oscillation of the nonlinear structures. In the case of a weakly magnetized plasma, the amplitude of the oscillations are found to be constant while they are modulated for a strongly magnetized plasma. The findings are compared with satellite observations.
Keywords: Auroral plasma; Oxygen ion beam; Fast Auroral SnapshoT satellite; Broadband electrostatic noise; Magnetosphere